The Geography Of Metaphors: Traveling, Learning, And The Writing Process - Whitman, Carleigh J. (My University, 2018)
Writing takes practice, much like any other activity in life. Usually, I’m more than willing to jump into any opportunity to write, letting my thoughts fall onto the page. The whole idea for my honors project, originally, centered on curating a collection of different examples of writing to use in my future secondary English classroom. Spoiler alert: that didn’t end up happening because life had other plans. What my honors project has become is an exercise in reflective writing. I adopted an informal tone, as I wanted my writing to reflect my thoughts as they occur in my head; what is on the page is no one’s voice but my own, as imperfect as it may be. Through my reflection, I have tried to synthesize my experience during my semester abroad by interspersing writing I produced while I was living in Ireland with writing from the months following my return to the States. Ultimately, I wanted my honors project to be an exploration into my psyche and what I have learned that will continue to affect me as I go through life, not an excuse for a wayward project gone awry. With that in mind, here it is: my qualitative dive into introspection.